Gravity and the behavior of unicellular organisms - Häder, Donat-Peter (Developmental and cell biology series, 2005)
Unicellular organisms use gravity as an environmental guide to reach and stay in regions optimal for their growth and reproduction. These single cells play a significant role in food webs and these factors together make the effects of gravity on unicellular organisms a fascinating and important subject for scientific study. In addition, they present valuable model systems for studying the mechanisms of gravity perception, a topic of increasing interest in these days of experimentation in space. This book reveals how single cells achieve the same sensoric capacity as multicellular organisms like plants or animals. It reviews the field, discussing the historical background, ecological significance and related physiology of unicellular organisms, as well as various experimental techniques and models with which to study them. Those working on the biology of unicellular organisms, as well as in related areas of gravitational and space science will find this book of value